CYBERGOGY-BASED LEARNING: A CASE STUDY AMONG UNIVERSITY OF MALAYA CONTINUING EDUCATION CENTER'S (UMCCED) STUDENTS - Zuraidah Abdullah,; Ramlan Mustapha,; Nurshahira Ibrahim,; Siti Norma Aisyah Malkan,; Muhammad Nasrul Hakim Roslan, (Journal of Islamic, Social, Economics and Development, 2024)
Cybergogy plays a significant role in the education sector, specifically in teaching and learning. Cybergogy is an educational approach that utilizes Information and Communication Technology (ICT) to empower learners. It is not limited by geographical location, time, cultural differences, or national boundaries. The rapid transition from traditional classroom to online teaching and learning has excluded the implementation of Cybergogy from the current educational process. The objective of this study is to determine the extent to which UMCCED student’s readiness towards Cybergogy learning in terms of cognitive, social, and emotional variables. This study employed a descriptive design with a quantitative approach. The study sample comprised 201 students from UMCCED at the Cyberjaya Malaysia campus. The research tools utilized in this study were a collection of modified questionnaires derived from previous research projects. The discovery suggests that technical students are well-prepared for online instruction. The data pertaining to emotional, cognitive, and social preparedness characteristics are predominantly at the medium and high levels. The research indicates that UMCCED students are prepared for online learning, as demonstrated by their readiness for cybergogy. Future research is suggested upon the conclusion of the current study.